Fruktosamin som markör för diabetes mellitus hos katt - Brandeker, Erika (2003)
Diabetes mellitus is characterised by persistent hyperglycemia in all species. Fructosamine is a glycated protein reflecting blood glucose concentration during the preceding weeks. It has become a valuable analysis to differentiate persistent hyperglycemia from transient stress induced hyperglycemia in cats. It is also used to evaluate current therapy in diabetic patients. Although fructosamine is a well accepted analysis, it is sometimes regarded with scepticism. According to present literature there are significant differences between fructosamine concentrations in healthy cats and in diabetics. There are, however, overlaps, which means that single healthy individuals can have elevated values and diabetics may have values in the normal range.